Fuel for growth and development. Issue 5 (October 2015) - Pullinger, John; Melamed, Claire; Bentley, George; Shortridge, Julie; Falconi, Stefanie; Zaitchik, Ben; Guikema, Seth; Larsen, Jacqueline Joudo; Datta, Monti Narayan; Bales, Kevin; Robineau, Delphine; Tranter, Matthew; et al.
Abstract : World Statistics Day is the ideal time to showcase diverse applications of data, and how the work of statisticians is helping improve the lives of people around the world. The next 20 pages offer merely a glimpse of the full range of problems to which statistical analysis is applied, despite touching on a wide range of issues: from economic development to trade and transport, data sharing, human rights and hunger. We begin, though, with a special introduction fromJohn Pullinger, the UK National Statistician and current chair of the UN Statistical Commission, on the importance of World Statistics Day